Análise fitoquímica e estudo biológico da espécie Pilocarpus pennatifolius Lemmaire - Carmo, Gabriele do (2014)
The purpose of this study was to conduct a phytochemical study of the crude extract of the leaves of the species Pilocarpus pennatifolius derived the genus Pilocarpus, popularly known as jaborandi or agouti-white. This species is widely distributed in the Americas, in the state of Rio Grande do Sul in natural plant formations in the central region and has use in folk medicine in the treatment of glaucoma and digestive diseases. In this work were isolated molecules of which the chromatographic profile were studied by column chromatography and TLC, the identification and confirmation of the compounds, by analysis of diffraction X-rays, NMR 1H and 13C one and two dimensional, rotation optical of index and fusion points. The bergapten 24 and xanthotoxin 25 compounds belonging to the class of furanocoumarins were isolated in the acid ether fraction with different solvent gradient (CHCl3-MeOH 1% for bergapten e CHCl3-MeOH 5% for xanthotoxin). The imidazole alkaloid G01-20 was first isolated in pennatifolius Pilocarpus species, derived from the basic fraction acetate gradient solvent of CHCl3-MeOH 15%. Throught the hydrodestilation was the extraction of essential oils of the species P.pennatifolius in the different seasons, with the intention of compare the chemically the same as seasonality. The main constituents were found -humolene and E-caryophyllene. While limonene manifests itself only the winter and summer at low concentrations. The antimicrobial activities of metabolites, fractions, extract and essential oils showed good antimicrobial potential against some microorganimos. The xanthotoxin metabolite when tested against their antioxidant capacity showed a good antioxidant potential.